Evidence for the Primary Role of Phytoplankton on Nitrogen Cycle in a Subtropical Reservoir: Reflected by the Stable Isotope Ratios of Particulate Nitrogen and Total Dissolved Nitrogen - Cai, Yangyang; Cao, Yingjie; Tang, Changyuan (Frontiers in Microbiology, 2019)
Knowledge about the primary factor controlling stable isotope ratios of particulate nitrogen (δ15NPN) and total dissolved nitrogen (δ15NTDN) in a subtropical reservoir can improve the understanding of regional and global nitrogen cycles. Taking Lianhe Reservoir as a representative subtropical reservoir, we studied the spatial and temporal distributions of δ15NPN andδ15NTDN and their relationships with the surrounding physicochemical factors and phytoplankton. The results showed that variations in δ15NPN and δ15NTDN followed seasonal thermal cycles. The values of δ15NTDN were inversely proportional to those of δ15NPN. PCA showed that phytoplankton cell density and pH were the primary drivers of the variation of δ15NPN (45.2 %). The primary factors influencing δ15NTDN were Chl a and phytoplankton cell density, which both indicated phytoplankton biomass. We also determined that the dominant species was Microcystis densa during the thermal stratification period and Staurodesmus aristiferus during the mixing period. Laboratory experiments showed that δ15NPN values in both M. densa (from 19.5 to 14.6 ‰) and S. aristiferus (from 19.4 to 16.0 ‰) media decreased significantly as the algal cells grew. Furthermore, the δ15NTDN values increased from 4.9 to 7.9 ‰ and from 4.7 to 6.9 ‰ in M. densa and S. aristiferus media, respectively, when the δ15NPN values decreased. These experimental results were consistent with field investigation results and indicated that variations in δ15NPN and δ15NTDN were mainly controlled by phytoplankton cell density, especially the cell density of the dominant species, in both the thermal stratification and mixing periods. The results also suggested that cell density, not phytoplankton species, was the key factor regulating the distribution of nitrogen stable isotopes. These results together indicated that phytoplankton cell density is the primary factor in the regulation of nitrogen stable isotope composition and that its influence is greater than that of other physical and chemical factors. This study provided detailed information supporting the primary role of phytoplankton in the nitrogen geochemical cycle and improved the understanding of biochemical processes in natural subtropical reservoirs.